Possibilities of Support for Reintegration of Mothers with Small Children - Győrváriné Tumpek, Gabriella; Kendefi, Miklós (Acta Carolus Robertus, 2022)
Today, more and more families in Hungary are having children, which is basically a big challenge for the employers if they want to keep their employees in long term. It puts parents - who want to return to their position later as workers with small children - in a difficult life situation, with all its circumstances. In our view, in addition to positive workplace discrimination, the methodology of career counseling can play an important role in their retention and integration. Hopefully, this new approach will be the future trend in the field of counseling, combining its different fields. How this can be a mutually beneficial, forward-looking and long-term solution is presented in a program based on the key competencies discovered of expectant mothers. The aim is to deepen self-definition and strengthen self-assessment, which have key importance for job retention.